2013
DOI: 10.1111/1442-1984.12025
|View full text |Cite
|
Sign up to set email alerts
|

Germination of Prosopis juliflora (Sw.) D.C. seeds at different osmotic potentials and temperatures

Abstract: The effects of osmolytes, osmotic potential (Ψs), temperature, and their interactions on the germinability, germination rate, and other germination parameters of the invasive shrub Prosopis juliflora, which grows in the semiarid environmental conditions of the Caatinga in northeast Brazil, were evaluated. To study the effects of polyethylene glycol (PEG) and NaCl stress and temperature on germination, two separate experiments were carried out at the Plant Ecophysiology Laboratory of the Federal University of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 48 publications
1
35
0
2
Order By: Relevance
“…The reduction of germination due to the increase in water deficit was also observed by Miranda et al (2014) in seeds of Prosopis juliflora (Sw.) D.C. These authors reported that, at the highest temperatures (35 and 40 ºC), the reduction was faster than at the lowest temperatures (25 and 30 ºC).…”
Section: Resultsmentioning
confidence: 67%
“…The reduction of germination due to the increase in water deficit was also observed by Miranda et al (2014) in seeds of Prosopis juliflora (Sw.) D.C. These authors reported that, at the highest temperatures (35 and 40 ºC), the reduction was faster than at the lowest temperatures (25 and 30 ºC).…”
Section: Resultsmentioning
confidence: 67%
“…The output results were compared with those generated by the spreadsheet described by Miranda et al (2014), Ranal et al (2009) and Joosen et al (2010). Feedback from users is welcome and will be used to improve the program and to correct unforeseen flaws.…”
Section: Test Software and Survey With Usersmentioning
confidence: 99%
“…Currently, there is a lack of information about the start time, rate, and uniformity of germination, which are essentially important for normally distributed seed population and for seed companies. This feature could be solved by the introduction of the mean germination time (MGT), uncertainty (U), and synchrony (Z) of germination (Miranda et al, 2014;Ranal and Santana, 2006). However, in this type of experiment the number of germination assays required is immense, which can lead to human error or misjudgment of seed treatments.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations